Bridging gender and youth studies - Learning from rural young women and men in central Uganda - Rietveld, Anne (Bioversity International, 2018)
Presented by Anne Rietveld (Bioversity International), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.